Accelerating DevSecOps on AWS - Swaraj, Nikit (Packt Publishing, 2022)
Build high-performance CI/CD pipelines that are powered by AWS and the most cutting-edge tools and techniques Key Features Master the full AWS developer toolchain for building high-performance, resilient, and powerful CI/CD pipelines Get to grips with Chaos engineering, DevSecOps, and AIOps as applied to CI/CD Employ the latest tools and techniques to build a CI/CD pipeline for application and infrastructure Book Description Continuous integration and continuous delivery (CI/CD) has never been simple, but these days the landscape is more bewildering than ever; its terrain riddled with blind alleys and pitfalls that seem almost designed to trap the less-experienced developer. If you're determined enough to keep your balance on the cutting edge, this book will help you navigate the landscape with ease. This book will guide you through the most modern ways of building CI/CD pipelines with AWS, taking you step-by-step from the basics right through to the most advanced topics in this domain. The book starts by covering the basics of CI/CD with AWS. Once you're well-versed with tools such as AWS Codestar, Proton, CodeGuru, App Mesh, SecurityHub, and CloudFormation, you'll focus on chaos engineering, the latest trend in testing the fault tolerance of your system. Next, you'll explore the advanced concepts of AIOps and DevSecOps, two highly sought-after skill sets for securing and optimizing your CI/CD systems. All along, you'll cover the full range of AWS CI/CD features, gaining real-world expertise. By the end of this AWS book, you'll have the confidence you need to create resilient, secure, and performant CI/CD pipelines using the best techniques and technologies that AWS has to offer. What you will learn Use AWS Codestar to design and implement a full branching strategy Enforce Policy as Code using CloudFormation Guard and HashiCorp Sentinel Master app and infrastructure deployment at scale using AWS Proton and review app code using CodeGuru Deploy and manage production-grade clusters using AWS EKS, App Mesh, and X-Ray Harness AWS Fault Injection Simulator to test the resiliency of your app Wield the full arsenal of AWS Security Hub and Systems Manager for infrastructure security automation Enhance CI/CD pipelines with the AI-powered DevOps Guru service Who this book is for This book is for DevOps engineers, engineering managers, cloud developers, and cloud architects. Basic experience with the software development life cycle, DevOps, and AWS is all you need to get started.